Bing Crosby rediscovered [videorecording (DVD)] - Crosby, Bing, 1903-1977; Trachtenberg, Robert; Tucci, Stanley ([Publisher not identified], 2014)
Bing Crosby was, without a doubt, the most popular and influential multi-media star of the first half of the twentieth century, pulling audiences in with his intimate, laid-back voice and innate charm. Narrated by Stanley Tucci and directed by Robert Trachtenberg, this film explores the life and legend of this iconic performer, revealing a personality far more complex than the image the public had only thought they'd known.